Exfoliation of graphite into graphene in polar solvents mediated by amphiphilic hexa-peri-hexabenzocoronene - Kabe, Ryota; Feng, Xinliang; Adachi, Chihaya; Muellen, Klaus (Chemistry - An Asian Journal, 2014)
A water-soluble surfactant consisting of hexa-perihexabenzocoronene (HBC) as hydrophobic aromatic core and hydrophilic carboxy substituents was synthesized. It exhibited a self-assembled nanofiber structure in the solid state. Profiting from the π interactions between the large aromatic core of HBC and graphene, the surfactant mediated the exfoliation of graphite into graphene in polar solvents, which was further stabilized by the bulky hydrophilic carboxylic groups. A graphene dispersion with a concentration as high as 1.1 mgL-1 containing 2-6 multilayer nanosheets was obtained. The lateral size of the graphene sheets was in the range of 100-500 nm based on atomic force microscope (AFM) and transmission electron microscope (TEM) measurements.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Graphene; Nanostructures; Polycyclic aromatic hydrocarbons; Self-assembly; Surfactants